2023
DOI: 10.1021/acsami.3c09452
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization with (3-Glycidyloxypropyl)trimethoxysilane (GOPS) as an Alternative to Blending for Enhancing the Aqueous Stability and Electronic Performance of PEDOT:PSS Thin Films

Peter O. Osazuwa,
Chun-Yuan Lo,
Xu Feng
et al.

Abstract: Organic mixed ionic−electronic conductors, such as poly (3,4ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), are essential materials for the fabrication of bioelectronic devices due to their unique ability to couple and transport ionic and electronic charges. The growing interest in bioelectronic devices has led to the development of organic electrochemical transistors (OECTs) that can operate in aqueous solutions and transduce ionic signals of biological origin into measurable electronic signals. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 72 publications
(151 reference statements)
5
6
0
Order By: Relevance
“…Numerous CPs have been utilized in the field of tissue engineering, including PPy, PANI, PEDOT, and poly(3-hexylthiophene) [ 22 ]. The conducting polymer PEDOT is commonly doped with PSS to form a stable aqueous suspension of particles [ 35 ]. Due to its exceptional chemical stability and conductivity, PEDOT finds applications in diverse fields including energy reserves, sensors, conductor electrode materials, biotechnology, and medicine [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous CPs have been utilized in the field of tissue engineering, including PPy, PANI, PEDOT, and poly(3-hexylthiophene) [ 22 ]. The conducting polymer PEDOT is commonly doped with PSS to form a stable aqueous suspension of particles [ 35 ]. Due to its exceptional chemical stability and conductivity, PEDOT finds applications in diverse fields including energy reserves, sensors, conductor electrode materials, biotechnology, and medicine [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The films sufficiently well adhered to the glass slide, thanks to the plasma treatment. However, to ensure a higher mechanical stability and adhesion, we would recommend using a glass surface treatment with an adhesive monolayer such as (3-glycidyloxypropyl)­trimethoxysilane (GOPS) . While this photoprinting experiment was not fully optimized, it showed that we can achieve patterns of conductive hydrogels with micron-scale resolution.…”
Section: Resultsmentioning
confidence: 99%
“…However, to ensure a higher mechanical stability and adhesion, we would recommend using a glass surface treatment with an adhesive monolayer such as (3glycidyloxypropyl)trimethoxysilane (GOPS). 62 While this photoprinting experiment was not fully optimized, it showed that we can achieve patterns of conductive hydrogels with micron-scale resolution. Higher resolution (down to submicrons) could be obtained by two-photon stereolithography.…”
Section: Acs Polymers Aumentioning
confidence: 99%
“…Figure 7 b shows that bands at 438, 988, and 1257 cm −1 are, respectively, assigned to C-O-C deformation, oxacyclic ring deformation, and C α –C α inter-ring stretching. Particularly, the characteristic band at 1428 cm −1 , attributed to symmetric C α = C β (-O) stretching, indicates a high degree of conjugation [ 49 ]. Furthermore, a shift from 1428 to 1438 cm −1 is observed, indicating a decrease in the concentration of charge carriers [ 50 ].…”
Section: Resultsmentioning
confidence: 99%